A Mycobacterial smc Null Mutant Is Proficient in DNA Repair and Long-Term Survival - Güthlein, Carolin (American Society for Microbiology (ASM), 2008)
SMC (structural maintenance of chromosomes) proteins play fundamental roles in various aspects of chromosome organization and dynamics, including repair of DNA damage. Mutant strains of Mycobacterium smegmatis and Mycobacterium tuberculosis defective in SMC were constructed. Surprisingly, inactivation of smc did not result in recognizable phenotypes in hallmark assays characteristic for the function of these genes. This is in contrast to data for smc null mutants in other species.